An inquiry into 'The nature of capital': with special reference to C.I.R. versus Middelman - Niland, Christopher Barlow (Department of Commercial Law, 2021)
Our Courts have, in many decisions stretching over decades, been faced with the problem of deciding whether the proceeds of the disposal of certain assets are revenue, or are of a capital nature. The assets which have given rise to the problem are those which one would normally consider to be capital in the hands of the taxpayer, but which may be held to have to have altered in character due to some action of the taxpayer, either by way of a change in the intention of the taxpayer regarding the asset in question, or by virtue of the method adopted by him in the disposal of the asset. The reported cases t dealing with this question arise mainly from the disposal of either shares or immovable property, although this has not always been the case. The principles involved in the inquiry remain the same, no matter what the nature of the asset is, but the application of those principles depends on a number of factors, including the nature of the asset, and of course, the circumstances of the taxpayer.